Antagonistic Relationship Between VEP Potentiation and Gamma Power in Visual Snow Syndrome. Issue 1 (29th November 2017) - Luna, Sebastian; Lai, Daniel; Harris, Alison
Abstract : Objective: Using a "double‐pulse" adaptation paradigm, in which two stimuli are presented in quick succession, this study examines the neural mechanisms underlying potentiation of the visual evoked potential (VEP) in visual snow syndrome. Background: Visual snow is a persistent visual disturbance characterized by rapid flickering dots throughout the visual field. Like the related condition of migraine with aura, visual snow has been hypothesized to arise from abnormal neuronal responsiveness, as demonstrated by a lack of typical VEP habituation to repeated visual stimulation. Yet the exact neural mechanisms underlying this effect remain unclear. Previous "double‐pulse" experiments suggest that typical VEP habituation reflects disruptive gamma‐band (50‐70 Hz) neural oscillations, possibly driven by inhibitory interneurons. Given that migraine has been associated with reduced cortical inhibition, we propose here that visual snow may likewise reflect diminished inhibitory activity, resulting in decreased gamma power following initial visual stimulation and concomitant potentiation of the subsequent VEP response. Methods: We compared VEP responses to double‐pulse adaptation in a 22‐year‐old man with a 2‐year history of visual snow versus a group of age‐ and gender‐matched controls ( N  = 5). The patient does not have a comorbid diagnosis of episodic migraine or migraine with aura, and controls had no personal or family history of migraine. Results: In contrast to the pattern of habituation observed in controls, visual snow was associated with persistent potentiation of the VEP response. Consistent with our predictions, time‐frequency analysis revealed reduced gamma‐band power following the initial stimulus in visual snow relative to controls. Conclusions: These results support an antagonistic interplay between gamma power and rapid neural adaptation, shedding new light on the neural mechanisms of VEP potentiation in visual snow.